Management of optic disc pit maculopathy: the European VitreoRetinal society optic pit study. Issue 6 (7th December 2021) - Iros, Mariano; Parolini, Barbara; Ozdek, Sengul; Gini, Giampaolo; Nawrocka, Zofia Anna; Ellabban, Abdallah A; Faramawi, Mohammed F.; Adelman, Ron; Sallam, Ahmed B.; ,
Abstract: Purpose: To evaluate a variety of techniques, and their anatomical and functional results, for the treatment of optic disc pit maculopathy (ODP‐M). A secondary aim was to report on results of secondary procedures in cases of initial failure or recurrence. Methods: Multicentre retrospective study of 95 eyes with ODP‐M, treated by 25 surgeons from 12 countries. Primary outcomes were anatomical resolution of subretinal fluid (SRF), intraretinal fluid (IRF) and visual acuity (VA) at 12 months. Results: Higher rates of SRF and IRF resorption were achieved in eyes treated with pars plana vitrectomy (PPV) compared to external laser with or without tamponade: 64/72 (88.9%) versus 8/14 (57.1%) for SRF (p = 0.003), and 50/59 (84.7%) versus 3/10 (30%) for IRF (p = 0.002). The addition of juxtapapillary laser or internal limiting membrane (ILM) peel during PPV did not improve SRF or IRF resolution. Pars plana vitrectomy (PPV) with tamponade and PPV with tamponade plus endolaser were associated with significant visual gain. In the former group, VA improved from a mean of logMAR 0.91 (20/162), to a mean of logMAR 0.52 (20/66) at 12 months; in the latter group, VA improved from a mean of logMAR 0.82 (20/132) to a mean of logMAR 0.47 (20/59) at 12 months. Retreatments were performed in 14 eyes (15.7%), only enhancing anatomical outcomes. Conclusion: Vitrectomy with tamponade had better final outcomes than external laser treatment with or without gas tamponade. Laser endophotocoagulation and ILM peel provided no additional benefit. A secondary treatment resulted in anatomical but not functional improvement.